Studying The Effect of Storage Conditions on The Fungal Growth in Infant Cereal Products at Local Market - Al-Diab, Dima; Sulaeman, Sheiam; Deeb, Dima Nizar (Latakia University Journal -Medical Sciences Series, 2020)
Infant cereals are the essential food given to babies after ablactation at the age of 6 months, because breast milk is no longer able to provide the infant with sufficient nutrients. These products consist mostly of rice and wheat cereals, and sometimes it could be flavoured with fruits ,honey, banana and vegetables. It is considered a source of minor and major nutrients, and it is susceptible to microbial contamination especially fungal growth due to it is grains composition. This study aims to evaluate the effect of storage conditions (such as temperature and duration) on the fungal growth. This study includes 28 samples of infant wheat and rice cereal products available in the local market. Results: there was slight change in the fungal counts and it should be noted that there is no Syrian standards fungal counts in infant cereals to compare with. تُعد أغذية الرُضّع المُصنَّعة من الحبوب الغذاء الأساسي الذي يُعطى للرّضيع بعد الفطام بدءاً من عمر 6 أشهر، لأن الحليب لا يعد قادراً على استكمال المتطلّبات التّغذويّة للرضّع. تُعتبر أغذية الرضّع المُصنّعة من الحبوب مصدراً للعناصر المغذّية الكبرى والصّغرى، إذ يدخل بتركيب هذه المحضّرات حبوب القمح والأرُز بشكل رئيسي كما يمكن أن تتواجد بشكل محضّرات قمح فواكه أو قمح عسل أو قمح موز أو أرُز خضار، وتُعتبر محضّرات أغذية الرضّع المصنّعة من الحبوب عُرضةً للتلوث بالأحياء الدّقيقة عموماً والفطور خصوصاً بسبب تركيبها الأساسي من الحبوب. تهدف هذه الدّراسة إلى مراقبة التّعداد العام للفطور ودراسة تأثير تغيّر شروط التّخزين من درجة الحرارة ومُدّة التّخزين على هذا التّعداد حيث شملت الدّراسة 28 عيّنة من مُنتجات أغذية الرضّع المصنّعة من حبوب القمح والأرُز المتوافرة بالسّوق المحليّة وتمّ تقييم تعداد الفطور عند فتح العبوة وبعدها خلال ظروف مختلفة وأظهرت الدراسة تغيراً طفيفاً في مستويات التعداد الفطري من دون وجود مواصفة قياسيّة سورية لمقارنة نتائجنا بها.